Resveratrol Protects Osteoblasts Against Dexamethasone-Induced Cytotoxicity Through Activation of AMP-Activated Protein Kinase - Wang L; Li Q; Yan H; Jiao G; Wang H; Chi H; Zhou H; Chen L; Shan Y; Chen Y (Dove Medical Press, 2020)
Liang Wang,1– 3,* Qiushi Li,4,* Haibo Yan,3 Guangjun Jiao,1 Hongliang Wang,1 Hai Chi,5 Hongming Zhou,1,6 Lu Chen,1 Yu Shan,1 Yunzhen Chen1,2 1Department of Orthopedics, Qilu Hospital, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People’s Republic of China; 2Shandong University Spine and Spine Cord Disease Research Center, Shandong University, Jinan, Shandong, People’s Republic of China; 3Department of Internal Medicine, Shandong Medical College, Linyi, Shandong, People’s Republic of China; 4Department of Orthopedics, Linyi People’s Hospital, Linyi, Shandong, People’s Republic of China; 5Department of Traumatic Orthopedics, Shandong Provincial ENT Hospital (Affiliated to Shandong University), Jinan, Shandong, People’s Republic of China; 6Department of Emergency Trauma Surgery, Linyi Central Hospital, Linyi, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yunzhen ChenDepartment of Orthopedics, Qilu Hospital, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People’s Republic of ChinaTel/Fax +86-531-82166531Email qilucyz@yeah.netPurpose: Glucocorticoids are used for the treatment of inflammatory diseases, but glucocorticoid treatment is associated with bone damage. Resveratrol is a phytoalexin found in many plants, and we investigated its protective role on dexamethasone-induced dysfunction in MC3T3-E1 cells and primary osteoblasts.Materials and Methods: MC3T3-E1 cells and primary osteoblasts were treated with dexamethasone in the presence/absence of different doses of resveratrol for 24 or 48 h. Then, 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyltetrazolium (MTT) and lactate dehydrogenase (LDH) assays were used to evaluate cell viability. Apoptosis was analyzed by a flow cytometry. An alkaline phosphatase (ALP) activity assay and Alizarin Red S staining were used to study osteoblast differentiation. Expression of osteoblast-related genes was measured by real-time reverse transcription-quantitative polymerase chain reaction (RT-qPCR). The AMP-activated protein kinase (AMPK) signaling pathway and mitochondrial expression of superoxide dismutase were evaluated by Western blotting. Intracellular reactive oxygen species (ROS), adenosine triphosphate (ATP) content, mitochondrial-complex activity, and mitochondrial DNA content were measured to evaluate mitochondrial function.Results: Resveratrol induced the proliferation and inhibited apoptosis of osteoblasts in the presence of dexamethasone. Resveratrol increased the ALP activity and mineralization of osteoblasts. Resveratrol also attenuated dexamethasone-induced inhibition of mRNA expression of osteogenesis maker genes, including bone morphogenetic protein-2, osteoprotegerin, runt-related transcription factor-2, and bone Gla protein. Resveratrol alleviated dexamethasone-induced mitochondrial dysfunction. Resveratrol strongly stimulated expression of peroxisome proliferator–activated receptor-γ coactivator 1α and sirtuin-3 genes, as well as their downstream target gene superoxide dismutase-2. Resveratrol induced phosphorylation of AMPK and acetyl-CoA carboxylase (ACC). Blockade of AMPK signaling using compound C reversed the protective effects of resveratrol against dexamethasone.Conclusion: Resveratrol showed protective effects against dexamethasone-induced dysfunction of osteoblasts by activating AMPK signaling.Keywords: resveratrol, dexamethasone, osteoblasts, AMPK, mitochondrial function